Harnessing nutrients and natural products for sustainable drug development against aging - Ding, Fuan; Yu, Ying; Zhang, Yan; Wei, Shibo; Han, Jung Ho; Li, Zhuo; Jiang, Hong-Bo; Ryu, Dongryeol; Park, Wonyoung; Ha, Ki-Tae; Geng, Li (Frontiers in Pharmacology, 2025)
Developing treatments for age-related diseases requires cost-effective and efficient approaches. Nutrients and natural metabolites offer safer alternatives to synthetic drugs. Aging increases the need for solutions that protect health and repair cells. Recent studies show that nutrients and natural products reduce oxidative stress, regulate metabolism, and influence longevity-related genes. This review focuses on vitamins, minerals, antioxidants, and natural products that improve healthspan and combat aging. It also discusses challenges such as standardization, clinical validation, and regulatory approval. Finally, emerging trends, such as personalized nutrition and advanced delivery systems, highlight the potential of these metabolites for addressing aging.